2003
DOI: 10.1097/00006982-200304000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Massive Spontaneous Choroidal Hemorrhage

Abstract: Massive spontaneous choroidal hemorrhage may be associated with hypertension, systemic anticoagulation, advanced age, and age-related macular degeneration. Final visual acuities are generally poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 25 publications
2
47
3
1
Order By: Relevance
“…13 Our results show that hypertension and advanced age might lead to ocular haemorrhage in patients receiving warfarin therapy, and that warfarin therapy should be considered as a risk factor for ocular bleeding. 10,14 In the present study we were not able to find any statistically significant association between ocular bleeding and gender, INR within the therapeutic range, the duration of warfarin therapy, the presence of diabetes 7 pointed out that aspirin therapy might double the risk of bleeding in patients taking warfarin. A recent large study by Shireman et al 15 reported that the risk of bleeding was moderately increased in elderly patients receiving combined warfarin and antiplatelet therapy.…”
Section: Biyik I Mercan O Ergene Et Al Ocular Bleeding Related Tcontrasting
confidence: 78%
See 1 more Smart Citation
“…13 Our results show that hypertension and advanced age might lead to ocular haemorrhage in patients receiving warfarin therapy, and that warfarin therapy should be considered as a risk factor for ocular bleeding. 10,14 In the present study we were not able to find any statistically significant association between ocular bleeding and gender, INR within the therapeutic range, the duration of warfarin therapy, the presence of diabetes 7 pointed out that aspirin therapy might double the risk of bleeding in patients taking warfarin. A recent large study by Shireman et al 15 reported that the risk of bleeding was moderately increased in elderly patients receiving combined warfarin and antiplatelet therapy.…”
Section: Biyik I Mercan O Ergene Et Al Ocular Bleeding Related Tcontrasting
confidence: 78%
“…Previous studies have shown that the incidence of retinal bleeding might increase with the presence of hypertension and advanced age. 7,9 In a recent study, Yang et al 10 showed that ocular bleeding, especially massive spontaneous choroidal haemorrhage, might be associated with hypertension, advanced age, systemic anticoagulation, atherosclerosis and agerelated macular degeneration. Our data are therefore consistent with previously reported research.…”
Section: Biyik I Mercan O Ergene Et Al Ocular Bleeding Related Tmentioning
confidence: 99%
“…[1][2][3][4]7 Our patient, who presented in an advanced stage of visual loss, had a recurrent suprachoroidal bleed but was eventually free of pain and was therefore managed conservatively.…”
Section: Commentmentioning
confidence: 87%
“…[1][2][3] Although PCV may cause subretinal haemorrhage, the authors are unaware of any previous reports on PCV causing massive and rapid suprachoroidal haemorrhage leading to secondary angle closure glaucoma. This may be because the diagnosis of PCV has increased in recent years with the advent of ICG angiography.…”
Section: Commentmentioning
confidence: 95%
See 1 more Smart Citation